A Comparison Between Ondansetron and Dexamethasone In The Prevention of Postoperative Nausea and Vomiting After Elective Overioctomy (oophorectomy) - layla Khalil Ibrahim (Diyala Journal of Medicine, 2018)
Background: Laparoscopic surgeries are associated with an appreciable high rate of post-operative nausea and vomiting, there is a trial to compare the effect of two drugs to minimize it.